DAMPAK FUNDAMENTAL DAN RISIKO SISTEMATIK TERHADAP HARGA SAHAM PERBANKAN INDONESIA - Dyatmiko, Ruruh (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Bank is represent one of the very sensitive sector to macro economic indicator. This mater make result share price of bank in stock exchange of Indonesia have very fluctuation and very dificult to predicted. The objective of this research is to understand fundamental factors dan systematic risk that influence securities price on banks sector. The fundamental factors used in this research are net interest margin, return on assets capital adequacy ratio, loan to deposit ratio and and systematic risk by using beta coefficient.  The sampling method uses is purposive sampling method. From thirty seven property companies that listed on stock exchange of Indonesia, only thirty six company were selected, that fulfilling sample criterion that were owning complete financial statement report of year 2009-2017, and listing in Indonesia Stock Exchange since 2009 up to 2017 and its commercialized active share in stock exchange. Hypotesis testing was done by the multiple regression analysis.